Positively charged membrane for removing low concentration Cr(VI) in ultrafiltration process. (December 2015) - Yao, Zhikan; Du, Shiyuan; Zhang, Yin; Zhu, Baoku; Zhu, Liping; John, Angelin Ebanezar
Abstract: To enhance the low concentration hexavalent chromium (Cr(VI)) removal performance in membrane filtration process, two novel positively charged ultrafiltration (UF) membranes were prepared. Firstly, a tertiary amine based UF membrane (TA membrane) was fabricated by blending tertiary amine containing block copolymer poly(methyl methacrylate- b -dimethylamino-2-ethyl methacrylate) (P(MMA- b -DMAEMA)) with poly (vinylidene fluoride) (PVDF) via a non-solvent induced phase separation (NIPS) process. Secondly, a quaternary ammonium based UF membrane (QA membrane) was prepared by surface quaternization on the TA membrane. The surface quaternization was confirmed by attenuated total reflectance Fourier transform infrared (ATR/FTIR) and X-ray photoelectron spectroscopy (XPS). While, the images from scanning electron microscopy (SEM) suggested that the quaternization had little effect on the membrane morphology. By measuring the water contact angle, surface charge, water permeation properties at different pH, Cr(VI) adsorption and desorption properties as well as the Cr(VI) removal performance in filtration process, the two membranes were compared. The results showed that compared with the TA membrane, the contact angle of the QA membrane decreased from 69° to 58°, the isoelectric point increased from pH 8.3 to more than pH 11, the fluxes changed slightly with the change of feed pH and the equilibrium Cr(VI) uptake at pH 7 increased from 6.96 mg/g to 63.17 mg/g, indicating enhanced hydrophilicity and surface positive charge, permeation stability, wide Cr(VI) removal pH range as well as the potential application in low concentration Cr(VI) removal.